2020
DOI: 10.1186/s13020-020-00368-0
|View full text |Cite
|
Sign up to set email alerts
|

Systemic osteoprotective effects of Epimedii Folium and Ligustri Lucidi Fructus in senile osteoporosis rats by promoting the osteoblastogenesis and osteoclastogenesis based on MLP-ANN model

Abstract: Background: Senile osteoporosis (SOP), which is caused by unbalanced bone remodeling, leads to significant economic and societal burdens globally. The combination of Epimedii Folium (EF) and Ligustri Lucidi Fructus (LLF) serves as a commonly-used prescription for SOP in Traditional Chinese Medicine (TCM). This study aimed to evaluate the osteoprotective effects of EF and LLF in combination on SOP rats based on the constructed multilayer perception (MLP)-artificial neural network (ANN) model. Methods: 15 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The least significant difference (LSD) test when the variances were equal or Tamhane's T2 test when the variances were not equal was used for comparisons between individual groups and to determine which means differed significantly statistically (P < 0:05). and retinoic acid-induced OP [15][16][17]23]. However, we still do not know the physical basis and effective components of EF, LLF, and EF&LLF.…”
Section: Western Blot (Wb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The least significant difference (LSD) test when the variances were equal or Tamhane's T2 test when the variances were not equal was used for comparisons between individual groups and to determine which means differed significantly statistically (P < 0:05). and retinoic acid-induced OP [15][16][17]23]. However, we still do not know the physical basis and effective components of EF, LLF, and EF&LLF.…”
Section: Western Blot (Wb)mentioning
confidence: 99%
“…Our previous researches have confirmed that EF&LLF has bone-protective effects by regulating bone remodeling in OVX-induced, natural aging-induced, glucocorticoidinduced, and retinoic acid-induced OP rats [15][16][17][18]. However, the effects of EF&LLF on the growth and differentiation of OBs and OCs and their communication at the cellular level are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a health checkup with bone mineral density measurement is essential to discover and identify osteoporosis as a standard means [Fardellone, 2020], while alteration of bone mineral density could be used as a useful intermediate endpoint to measure the risk of bone fracture and its reduction [Shevroja et al, 2021]. During the aging process, bone mineral density loss occurs [Tang et al, 2020]. Our current study confirmed that the bone mineral density of the left femur and L5 vertebral body was lower in the Aged rats than that in the Young rats.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of SOP involves the use of drugs inhibiting bone resumption clinically, but long-term use of these drugs can result in some complications, which limit their clinical application [ 4 ]. Recently, more and more scholars attach increasing attention to the osteoprotective effect of traditional Chinese medicine on treating SOP [ 5 ].…”
Section: Introductionmentioning
confidence: 99%